P462Metabolic control of microvascular networks: oxygen sensing and beyond. (15th July 2014) - Reglin, B; Pries, AR
Abstract: Purpose: Metabolic regulation of blood flow is central to guarantee adequate substrate supply of tissues and microvascular network stability. Vascular reactions to local oxygenation are assumed to match blood supply to tissue demand in steady state and in response to exercise and/or tissue hypoxia via negative feedback regulation: Low oxygen tension is assumed to induce the release of vasoactive substances which trigger increase of vessel number and diameter and thus of blood flow and oxygen supply (angioadaptation). Here, we try to integrate experimental and modelling findings to derive general schemes of metabolic regulation of angioadaptation, with a focus on control of vessel diameter. Methods: The different components and signalling chains of feedback control of vessel diameter were analysed with respect to their suitability to result in functionally adequate and stable complex vascular networks under steady state and non-steady state conditions. Results and Conclusions: A functional scheme of metabolic regulation is derived considering a) main requirements for vascular beds: sufficiently low diffusion distances between vessels and tissue cells, sufficiently homogenous perfusion under steady state conditions, adequate perfusion increase during increased demand, b) possible biological mechanisms: angiogenesis, structural diameter adaptation, change of vessel tone, and c) implementation of these mechanisms via feedback loops on different time scales. The following hypotheses are proposed: 1) In addition to oxygen dependent metabolic signalling, metabolic vascular regulation independent of local oxygenation or metabolic situation is established by the 'dilution effect'. 2) Control of resting vessel tone, and thus perfusion reserve, which has been shown to differ between tissues, can be explained by vascular responses to transient phases of insufficient blood supply: 'vascular memory'. 3) While for steady state adjustment of luminal vessel diameter a location of structures producing metabolic signals in or near to the vessel wall is optimal, signalling by red blood cells may be well suited to amplify perfusion during transient increases of tissue oxygen demand.